A Study of Protection Method for Hybrid Multiterminal UHVDC Lines Based on CEEMDAN–Teager Energy Operator - Xing, Chao; Wang, Long; Bi, Guihong; Chen, Shilong; Gao, Jingye; Che, Yanbo (Frontiers in Energy Research, 2022)
In the research, a protection scheme for hybrid multi-terminal UHVDC lines based on CEEMDAN and teager energy operator is proposed. The fault direction criterion is proposed according to the polarity difference of sudden variable of mode component of current line on both sides of T zone after fault of EHV multi terminal Hybrid DC system. When the fault is located on the left or right side of T zone, CEEMDAN is used to decompose the mode component of fault transient current and obtain the intrinsic mode function (IMF component) at different local characteristic time scales. Then, the teager energy operator is used to calculate the instantaneous energy of current high-frequency IMF1 component. Finally, the faults inside and outside the line are judged by comparing the maximum value of current high-frequency IMF1 instantaneous energy with the setting value. When the fault is located in the T zone, it is determined as a fault outside the line zone. The protection scheme of hybrid multi-terminal UHVDC lines is given. The simulation model of kunliulong hybrid multi-terminal UHVDC lines system is built in PSCAD / EMTDC simulation platform, and the proposed protection method is verified. A large number of simulation results show that the protection scheme has certain anti transition resistance ability and high reliability.